2016
DOI: 10.1038/aps.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Betulin attenuates atherosclerosis in apoE−/− mice by up-regulating ABCA1 and ABCG1

Abstract: Aim: Betulin is a pentacyclic triterpenoid isolated from the bark of yellow and white birch trees with anti-cancer and anti-malaria activities. In this study we examined the effects of betulin on atherosclerosis in apoE -/-mice and the underlying mechanisms. Methods: Murine macrophage RAW264.7 cells and human monocyte-derived THP-1 cells were tested. Foam cell formation was detected with Oil Red O staining. Cholesterol efflux was assessed using [3 H]-cholesterol efflux assay. The expression of ATP-binding cass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Betulinic acid was reported to be a potent pharmacological inhibitor of ACAT1 and ACAT2 (Lee et al, 2006), suggesting its potential utility in reduced CE accumulation. Moreover, an in vivo study was done using ApoE -/mice in which increased ABCA1 expression and enhanced fecal cholesterol excretion were observed upon long-term administration of betulin (40 mg/kg), along with suppressed macrophage-positive areas in the aortic sinuses (Gui et al, 2016). Another study confirmed that betulinic acid (50 mg/kg) reduced atherosclerotic lesions and reduced TG, TC, and LDL-C levels in ApoE 2/2 mice (Zhao et al, 2013a).…”
Section: B Terpenoidsmentioning
confidence: 82%
See 2 more Smart Citations
“…Betulinic acid was reported to be a potent pharmacological inhibitor of ACAT1 and ACAT2 (Lee et al, 2006), suggesting its potential utility in reduced CE accumulation. Moreover, an in vivo study was done using ApoE -/mice in which increased ABCA1 expression and enhanced fecal cholesterol excretion were observed upon long-term administration of betulin (40 mg/kg), along with suppressed macrophage-positive areas in the aortic sinuses (Gui et al, 2016). Another study confirmed that betulinic acid (50 mg/kg) reduced atherosclerotic lesions and reduced TG, TC, and LDL-C levels in ApoE 2/2 mice (Zhao et al, 2013a).…”
Section: B Terpenoidsmentioning
confidence: 82%
“…One study indicated that betulinic acid may induce cholesterol efflux through blocking the NF-kB-miRNA-33s-ABCA1 signal pathway in LPS-treated macrophages (Zhao et al, 2013a). Consistently, in both RAW264.7 and THP-1 cells, betulin (a betulinic acid derivative) significantly increased ABCA1/ABCG1-mediated cholesterol efflux via suppressing the expression of SREBPs, which bind to E-box motifs in the ABCA1 promoter (Gui et al, 2016).…”
Section: B Terpenoidsmentioning
confidence: 92%
See 1 more Smart Citation
“…Foam cells were confirmed by oil red O staining according to previous study. Images were taken from at least three randomly fields using IX73 microscopy (Olympus, Japan) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple independent groups in a study (e.g., different terpenoid doses) were considered separate datasets. In eleven studies [19, 20, 24, 26, 28, 33, 34, 3840, 42], multiple groups that tested different terpenoid doses were compared to a single control group. In order to avoid an artificial increase in sample size in the pooled analysis, the number of animals in the control group for each study was divided by the number of comparator groups.…”
Section: Methodsmentioning
confidence: 99%